Co‐transport of Pesticide Acetamiprid and Silica Nanoparticles in Biochar‐Amended Sand Porous Media. Issue 5 (1st September 2016) - Wang, Hong; Huang, Yuanfang; Shen, Chongyang; Wu, Junxue; Yan, An; Zhang, Hongyan
Abstract : The role of biochar as a soil amendment on the transport of acetamiprid, a widely used neonicotinoid pesticide, is little known. We conducted saturated column experiments to examine cotransport of acetamiprid and silica nanoparticles (NPs) in pure and biochar‐amended sands. Retention of acetamiprid was minor in the pure sand, whereas application of biochar in the sand significantly increased retention. Retention was greater at lower ionic strengths and near neutral pH values and was attributed to biodegradation and sorption through π–π interaction and pore filling. The convection–diffusion equation with inclusion of first‐order sorption, desorption, and degradation well described the transport of acetamiprid in the biochar‐amended sand. The simulation results show that the sorption rate did not change with pH. This is because the acetamiprid is nonionic and cannot be bonded with the biochar by protonation or deprotonation. The desorption rate was independent of variation of solution chemistry, indicating that desorption was a physical process (i.e., pore diffusion). Application of biochar in the sand had little influence on the transport of silica NPs in NaCl but caused complete attachment in CaCl2 . Energy dispersive X‐ray spectroscopy suggested that the enhanced attachment was due to cation bridging between silica NPs and functional groups in biochar by the Ca 2+ . The co‐presence of acetamiprid and silica NPs in the solutions enhanced transport of acetamiprid and NPs in the biochar‐amended sand by competing for the binding sites on the biochar surfaces. Core Ideas: We examined cotransport of acetamiprid and silica nanoparticles in biochar‐amended sand. Amendment with biochar significantly increased the removal of acetamiprid. The removal of acetamiprid by biochar was attributed to biodegradation and sorption. Silica nanoparticles were favorably attached on biochar surfaces in 2:1 electrolyte. The presence of silica nanoparticles enhanced transport of acetamiprid.